Factors Influencing the Intrinsic Value of SSI Stocks - Anh, Pham Thi Van (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Based on current research on stock analysis and valuation in Vietnam, there are various gaps in research groups studying the analysis and selection of valuation methods that are most suitable for practical application in the domestic stock market, particularly with regard to SSI stocks. Using the Free Cash Flow to Equity (FCFE) and Dividend Discount Method (DDM) approaches, the author identifies the resources of SSI Company for the years 2024 to 2026. However, the intrinsic value of SSI stocks is currently not accurately priced due to both objective and subjective factors outlined in the empirical section. Therefore, the author proposes specific solutions for the company and the state.